PENERAPAN STANDAR ISO 9001:2015 SISTEM MANAJEMEN MUTU PADA PT PLN (PERSERO) UPDK MAHAKAM UL PLTGU TANJUNG BATU - Sandy Dwi Prasetyo; Bambang Irawan; Fajar Apriani (Jurnal Paradigma (JP), 2020)
This study aims to identify and describe the application of the ISO 9001: 2015 Quality Management System standard and to identify the implementation of the Quality Culture contained in PT PLN (Persero) UPDK Mahakam UL PLTGU Tanjung Batu. The type of research used is descriptive qualitative data collection using observation, interviews, and literature studies. The data analysis technique used is an interactive model. The results showed that the implementation of the Quality Management System at PT PLN (Persero) UPDK Mahakam UL PLTGU Tanjung Batu refers to the principles and ten clauses required by the ISO 9001: 2015 Quality Management System standard. The results showed that the implementation of the Quality Management System at PT PLN (Persero) UPDK Mahakam UL PLTGU Tanjung Batu went well. A company's quality culture supports the implementation of the policy. However, labor limitations, employee consistency, and lack of socialization regarding implementing ISO 9001: 2015 are still obstacles experienced by companies.Keywords: Quality Management System, ISO 9001: 2015, Quality Culture, PLN Management